Identification of Generative AI Usage Profiles and Implications for Critical Thinking Skills in Physics Learning - Aminudin Zakaria; Budi Jatmiko; Binar Kurnia Prahani; Cahyo Febri Wijaksono (JPPS (Jurnal Penelitian Pendidikan Sains), 2026)
Objective: This study aims to map students' GenAI usage profiles during physics learning. In addition, it examines the correlation between these variables and students' critical thinking skills in physics learning. Method: A non-experimental, quantitative, ex post facto design was employed. This design captures phenomena that occur naturally without any intervention. The research instruments consisted of questionnaires and tests. Data were analyzed using descriptive statistics, the Kruskal–Walls test, and Spearman’s correlation test. Results: Students tend to accept answers from GenAI quickly during physics learning. Only a small proportion are accustomed to questioning, verifying, and evaluating GenAI-generated answers. There are differences in critical thinking skills among groups of students with different patterns of GenAI use, with an ε2 of 0.410. The profile of GenAI usage is positively correlated with critical thinking skills, with a correlation coefficient of 0.525, indicating a moderate relationship. Novelty: This study contributes by revealing students' GenAI usage profiles in physics learning and by providing empirical evidence that the quality of ethical and reflective use has a strong influence and is positively correlated with critical thinking skills.